Analysis of the Ability to Solve Mathematical Problems with the Distance Learning Method - Aprillianti Kanida (IAIN BENGKULU, 2020)
The aim of this researches is to find out the problem solving ability of VII grade Al-Atiqiyah junior high school students in Sukabumi with Square topics. The research was conducted on a limited subjec of 6 people.this research is a descriptive qualitative research. The instrument used in the form of 4 item description test questions. Based on research using the Polya procedure the following result were obtained: 1) at the stage of understanding the subject matter the researcher doesn;t provide information contained in the problem. 2) in the stage of designing a problem the subjec can carry out the stages well because it can write strategies in the form of formulas that will be used in doing the desgn. 3) In this stage, this subject can carry out this stage well, because it can be done a strategy to solve the problem given 4) In the stage of re-examining the results of all research subjects could not reach this stage because the research subjects did not write down conclusions and criticisms at the end of the answer.